Power dynamics in families affected by parental alienation. Issue 4 (28th June 2021) - Harman, Jennifer J.; Maniotes, Christopher R.; Grubb, Caitlyn
Abstract: The purpose of this study was to apply interdependence theory to understand the power dynamics in families affected by parental alienation. We hypothesized that the power dynamics between alienating and alienated parents are imbalanced such that this form of family violence (Harman et al., 2018) more closely resembles intimate terrorism than situational couple violence, where power dynamics are more similar between partners. We also hypothesized that shared parenting custodial arrangements would afford more power to targeted parents than unequal parenting plans and provide them with more opportunities for action. A qualitative analysis of transcripts from interviews with targeted parents of alienating behaviors ( n = 79) using interdependence theory as a framework found support for our hypotheses: most situations described by parents were of asymmetric dependence, with power concentrated almost exclusively with the alienating parent, and/or were direct challenges made by the alienating parent to gain control over their children and the targeted parent. In addition, the proportion of situations in which asymmetries in power were described was highest when the alienating parent had primary or sole custody of the children. Discussion focuses on the need to better understand and consider the role of power in the assessment of parental alienation so that appropriate and effective interventions may be implemented to protect children and their family members.